Awareness of Geriatric Services among North Indian Graduate Medical Students - Insights for Planning Training in Geriatric Medicine - Fatima, Zeba; Lahari, Telagamsetti Sesha Sai; Pandey, Aditi; Chakrabarti, Sankha Shubhra; Kaur, Upinder (Journal of the Indian academy of geriatrics, 2025)
Abstract Background: The older population is rapidly increasing in India. We aimed to understand the perception of graduate medical students toward geriatric medicine services, which might aid in future geriatric curriculum planning. Materials and Methods: The current study is a cross-sectional questionnaire-based survey that was conducted in a major tertiary university hospital in North India. Final-year graduate medical students and medical interns were included in this survey after obtaining written informed consent. Results: One hundred and fifty-two medical students (91 final year and 61 interns) were interviewed. The majority (90.8%) were aware of the existence of geriatric health services (GHS). One hundred and forty-nine (98%) agreed to the need for a separate GHS. The important reasons, as per the students, were physiological differences (40%), multimorbidity (22.4%), and atypical clinical presentations in older persons (20.4%). The majority (70.8%) of students had poor knowledge of the role of a pharmacologist in GHS. One hundred and thirty-seven (90.1%) students had poor awareness of medical institutions providing geriatric residency programs. Nearly two-thirds of the students were willing to join such programs, but it was the least preferred clinical choice. Fewer job prospects (46.1%) and lack of public awareness (19.2%) were the most common reasons for unwillingness. Conclusions: Revisions are needed in the teaching curriculum of Indian medical students with an emphasis on a multifaceted approach to older persons' health care. The career prospects of students pursuing the subject should be strengthened.